2019
DOI: 10.5334/irsp.211
|View full text |Cite
|
Sign up to set email alerts
|

The Face of Sexualization: Faces Wearing Makeup are Processed Less Configurally than Faces Without Makeup

Abstract: Objectification Theory (Fredrickson & Roberts, 1997) suggests that women are reduced to their bodies and physical appearance in Western cultures, as illustrated by the pervasive use of sexualization in the media. Sexualization is a set of features that emphasize sexiness through a focus on body parts (e.g., women wearing revealing clothing) and face parts (e.g., flashy lipstick and "smoky eyes": Smolak, Murnen, & Myers, 2014). Content analyses of advertisements revealed that women's bodies and faces are freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Moreover, adornments in the form of piercings, makeup, tattoos, and coverings are common. Cultural practices such as heavy makeup and face masks have been shown to reduceconfigural processing (Bernard et al, 2019). It is important to highlight how cultural norms may impair our social abilities within these contexts.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, adornments in the form of piercings, makeup, tattoos, and coverings are common. Cultural practices such as heavy makeup and face masks have been shown to reduceconfigural processing (Bernard et al, 2019). It is important to highlight how cultural norms may impair our social abilities within these contexts.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research found that sexualized bodies, akin to objects, are visually processed less globally (Bernard et al 2018a(Bernard et al , 2018dBernard et al 2019b) and more locally (Bernard et al 2018a) than nonsexualized bodies at a neural level (for a review, see Bernard et al 2018c). Importantly, it has been recently found that faces with heavy makeup are processed less configurally than faces without makeup (Bernard et al 2019a). Future investigations might use such paradigms to assess whether diminished configural processing is a cognitive mechanism driving the CDH.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…A more recent study carried out among 985 adults in the U.S., a country where cosmetic surgery is very popular, also shows that cosmetic surgery patients are seen as less warm, moral, and competent in relation to non-patients (Bonell et al, 2020). Some may consider cosmetic surgery immoral due to perceiving that it can harm physical and psychological health, as described above (e.g., Bonell et al, 2020); however, since women who wear makeup can also be seen as less competent, warm, and moral (e.g., Bernard et al, 2019Bernard et al, , 2020Kellie et al, 2021), it is reasonable to assume that people's negative attitudes toward cosmetic surgery may be attributed more to factors associated with beauty enhancement.…”
Section: Cosmetic Surgerymentioning
confidence: 97%